Comply With The Law and Deal With Fake Bank Encounters To Improve Banking Security - Risky Sukoy Sitindaon; July Esther; Debora Debora (International Journal of Law and Society, 2025)
These studies aim to determine which rules apply to the criminal act of currency counterfeiting. According to this perspective, a unique regulation governing the flow and counterfeiting of rupee currency is necessary for the development and strengthening of the financial sector. Standard research methodology based on statutory regulations is the methodology used. To answer legal problems, this approach uses research methods that examine and analyze the law as a basis. This can be in the form of criteria, rules, principles, theories and other literature. The results of the study show that legal regulations are in place to deal with currency counterfeiting, the weaknesses lie in a lack of understanding and tools to detect them and a lack of coordination between society and related institutions as well as a weak understanding of the law in society.